Hubungan Antara Kebiasaan Aktivitas Fisik dengan Indeks Massa Tubuh (Imt) pada Mahasiswa Fk-Uwks Angkatan 2016 dan 2017 - NOER KUMALA INDAHSARI; MOCH. IRFAN MAHALI (Universitas Hang Tuah, 2019)
Abstract Background: Being overweight in a person increases the risk of developing degenerative diseases, including diabetes mellitus which is still the most common cause of death, thus maintaining a normal weight allows a person to reach a longer life expectancy. One of the activities that can make normal weight is physical activity. The Body Mass Index (BMI) is a simple, inexpensive and easy method of assessing a person's nutritional status, but BMI can’t measure body fat directly. So that in this study activities will be carried out to get a relationship between physical activity with BMI for FK-UWKS students 2016-2017. Methode: 124 respondents from the 2016 and 2017 FK-UWKS students and taken randomly. The research method used was an analytic observational study with a cross sectional study. Data taken includes BMI, and physical activity. Statistical test with Spearman correlation test (x2). In the early stages of the study anthropometric measurements were carried out to determine Student BMI. Physical activity is measured by recalling activities that students do every day. Results: groups that always carried out physical activity were 24 respondents who had a normal body mass index, while the group that had never carried out physical activity had 57 respondents with a body mass index with details (3 respondents with less BMI, 11 respondents with normal BMI, 30 respondents with excessive BMI and 13 respondents with Obesity BMI)as well as groups that sometimes carried out physical activities totaling 43 respondents had a relatively normal body mass index. Conclution: There is a relationship between physical activity and the Body Mass Index in the 2016 and 2017 FK-UWKS students